ANALISIS KONTRIBUSI DAN POTENSI PENERIMAAN JASA PARKIR TEPI JALAN UMUM TERHADAP PENDAPATAN ASLI DAERAH (PAD) - Andi Widiawati (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This research aims to determine (1) how much contribution of service park on the street to the income of local own in Makassar, (2) how much potential of service park on the street revenues. This research aims made with quantitative of descriptive method, whereas the method of data collection is done by observation, interview, and literature study. Location of observation is done at one of area park in Asindo area with three park point to be aims sample. The sampling method using purposive random sampling techniques. Taking sample hoped can substitute park point in asindo area. This result of research indicate that (1) service of on the street parking has big contribution to park service. (2) until five (5) years, 2007-2011 Contribution of service park on the street to area service and the income of local own is fluctuative. (3) Potential of revenue from observation is bigger than realization of revenue which is deposited in Region Company of Park Makassar Raya, with assumption turn over are devided by three level are optimist (1 hour), moderate (2 hour), and pessimist (4 hour) .